Proapoptotic gene therapy and chemosensitivity of cancer cells - Rzońca, Sylwia; Małecki, Maciej (Contemporary Oncology/Współczesna Onkologia, 2009)
According to the data for the year 2008, 65.2% of all gene therapy protocols concern cancer diseases. Transfer of therapeutic genes are attempted for modification, repair, or inhibition of natural cellular mechanisms, whose dysfunction is observed in cancer cells. Gene therapy may provide an alternative to standard therapies, or complement them, increasing their effectiveness. Many changes take place at the cellular and genetic level in cancer cells, causing resistance. These relate to the activation of ATP-dependent pumps, changes in the distribution of drugs or mutations in genes associated with the apoptosis. Restoring the function of proapoptotic genes can affect the sensitivity of cancer cells to drug agents. The attempts described in this paper to overcome resistance of cancer through the transfer of proapoptotic related genes concern several groups of factors. The first group, TNF family receptors, is involved in activation of the extrinsic apoptotic pathway. Transfer, into cancer cells, of additional copies of the correct form of the receptor or its ligands, sensitizes them to anticancer agents. In the case of drug-induced “caspase-dependent” apoptosis, increased sensitivity to chemotherapy is achieved through the transfer of genes encoding caspases. Increased expression of inhibitors of apoptosis IAP and negative regulators of Bcl-2 causes resistance to drugs. Turning off these genes through the transfer of antisense oligonucleotides increases the sensitivity of cancer cells to chemotherapeutics. Several attempts have been made to restore the function of TP53 in cancer. The presence of mutated form of this transcriptional factor contributes to chemoresistance